S157-a structured early intervention program in patients with predicted poor long-term outcome following bariatric surgery: a prospective randomized study - Drakos, Panagiotis; Volteas, Panagiotis; Seeras, Kevin; Humayon, Shabana; Flink, Benjamin; Yang, Jie; Zhu, Chencan; Spaniolas, Konstantinos; Talamini, Mark; Pryor, Aurora (Surgical endoscopy, 2022)
Background Early postoperative weight loss can be predictive of one-year outcomes. It is unclear if poor performers identified in the first post-operative month can have improvement in outcomes with additional support and education. Purpose To evaluate the impact of a structured targeted support program for patients with lower-than-average early post-operative weight loss on 1-year outcomes. Methods This was a prospective randomized study of bariatric surgery patients who experienced less than 50th percentile excess body weight loss (%EWL) at 3 weeks. Subjects with EWL < 18% were randomized into two groups: an intervention (IV) arm or a control (NI, no intervention) arm. The IV arm was offered a program with 7-weekly behavioral support sessions, while the NI patients received routine post-operative care. Results A total of 128 patients were randomized: 65 NI and 63 IV. In the IV group, 20 attended all sessions, 7 attended < 4, and 36 did not participate. There was no difference in baseline demographics, procedure type, or BMI. At 1 year, there was no difference in %EWL (ratio 0.993, 95% CI 0.873, 1.131), %EBMIL (ratio 0.997, 95% CI 0.875, 1.137), and %TWL (ratio 1.016, 95% CI 0.901, 1.146) between groups. A subgroup analysis including only the subjects who participated in all seven sessions showed similar results. Conclusion Patients who present with suboptimal weight loss early after bariatric surgery do not experience a significant weight loss improvement with a structured behavioral support program. Importantly, despite being alerted to their poor early weight loss, patients demonstrated poor adherence to the proposed interventions.